Audit of HIV testing frequency and behavioural interventions for men who have sex with men: policy and practice in sexual health clinics in England. Issue 5 (7th January 2013) - Desai, Monica; Desai, Sarika; Sullivan, Ann Kathleen; Mohabeer, Malika; Mercey, Danielle; Kingston, Margaret A; Thng, Caroline; McCormack, Sheena; Gill, O Noel; Nardone, Anthony; ,
Abstract : Background: National guidance recommends targeted behavioural interventions and frequent HIV testing for men who have sex with men (MSM). We reviewed current policy and practice for HIV testing and behavioural interventions (BI) in England to determine adherence to guidance. Methods: 25 sexual health clinics were surveyed using a semistructured audit asking about risk ascertainment for MSM, HIV testing and behavioural intervention policies. Practice was assessed by reviewing the notes of the first 40 HIV-negative MSM aged over 16 who attended from 1 June 2010, in a subset of 15 clinics. Results: 24 clinics completed the survey: 18 (75%) defined risk for MSM and 17 used unprotected anal intercourse (UAI) as an indication of high risk. 21 (88%) offered one or more structured BI. Of 598 notes reviewed, 199 (33%) MSM reported any UAI. BI, including safer sex advice, was offered to and accepted by 251/598 (42%) men. A low proportion of all MSM (52/251: 21%) accepted a structured one-to-one BI as recommended by national guidance and uptake was still low among higher risk MSM (29/107: 27%). 92% (552/598) of men had one or more HIV test over a 1-year period. Conclusions: In 2010, the number of HIV tests performed met the national minimum standard but structured behavioural interventions were being offered to and accepted by only a small proportion of MSM, including those at a higher risk of infection. Reasons for not offering behavioural interventions to higher risk MSM, whether due to patient choice, a lack of staff training or resource shortage, need to be investigated and addressed.